Natural Language Processing and Chinese Computing Third CCF Conference, NLPCC 2014, Shenzhen, China, December 5-9, 2014. Proceedings - Zong, Chengqing; Nie, Jian-Yun; Zhao, Dongyan; Feng, Yansong (Springer eBooks, 2014)
This book constitutes the refereed proceedings of the Third CCF Conference, NLPCC 2014, held in Shenzhen, China, in December 2014. The 35 revised full papers presented together with 8 short papers were carefully reviewed and selected from 110 English submissions. The papers are organized in topical sections on fundamentals on language computing; applications on language computing; machine translation and multi-lingual information access; machine learning for NLP; NLP for social media; NLP for search technology and ads; question answering and user interaction; web mining and information extraction.